Reusable Laryngeal Tube Suction: Standard Insertion Technique Versus Two Modified Insertion Techniques for Patients with a Simulated Difficult Airway - Santosh Devi; Robina Nazir; Rajesh Mahajan; Jasmeen Chowdhary; Neha Sharma; Ajay Gupta (JK Science)
Background and Aims: The Laryngeal Tube Suction II (LTS-II) is a commonly used supraglottic airway device for routine and emergency airway management. It has been utilized in patients with unstable cervical spines, but successful insertion may require additional maneuvers. This study aimed to compare the success rate of LTS-II insertion using three techniques: standard insertion technique (SIT), SIT with jaw thrust (SIT-JT), and SIT with laryngoscopy (SIT-LS) in patients with simulated difficult airways under manual inline stabilization (MILS). Methods: A randomized parallel-group trial was conducted. The primary outcome was the success rate of LTS-II insertion across the three groups. Secondary outcomes included time to placement, number of attempts, ease of insertion, attempts at gastric tube insertion, oropharyngeal leak pressure at 5 minutes, and airway morbidity. Results: The overall success rates were 84.78% (SIT), 95.75% (SIT-JT), and 97.78% (SIT-LS). First-attempt success rates were 60.86%, 85.11%, and 86.67%, respectively. Mean insertion times were 48.3 ± 21.44 s (SIT), 36.62 ± 15.77 s (SIT-JT), and 35.87 ± 9.78 s (SIT-LS). Conclusion: LTS-II is an effective airway rescue device for patients with cervical spine injuries. Maneuvers like jaw thrust and laryngoscopy improve success rates and reduce insertion time until definitive airway management is available.